Retirement planning confidence of private sector employees in Kuantan, Pahang / Adibah Athirah A.Razak - A.Razak, Adibah Athirah (2017)
Malaysia is one of the developing country which also can stands together with other developed country in this world. However, it is quite disappointing when according to Employment Provident Fund (EPF), there were only 22 percent from 6.7 million active contributors have enough funds to retire. Moreover, it is also stated that one of the cause of this situation happens is because of Malaysia's low salary structure. This can be strengthen by 89 percent of the working population earns below than RM 5,000. This is a serious problem to be catered and everyone must do something in order to secure their retirement life. According to previous research conducted, it is proven that private sector employees were confident pertaining to retirement planning as they are financial literate, have clear goals and their positive attitude towards retirement. Thus, this study was conducted to discover whether private sector employees in Kuantan, Pahang are confident about their retirement planning. This study had been using retirement planning confidence of private sector employees as dependent variable, while for independent variables are financial literacy, goal clarity and attitude towards retirement. The results from this study shows that all independent variables are accepted which are the p value is below than 0.05. Hence, all independent variables in this study which are financial literacy, goal clarity and attitude towards retirement are significant and can be conclude that private sector employees in Kuantan, Pahang are confident regarding their retirement planning.